Digital Supply Chain Finance Model in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The chapter aims to study  and to evaluate digital supply chain finance model in Thailand. The samples in the research study consisted of ten purposively selected experts consisted of three experts on supply chain, five experts on Digital Technology and three experts on the finance. Data were analysed by arithmetic mean and standard deviation. The research findings model seven elements namely main components, Buyer, supplier , Bank or Financial Institution. The ten experts agree that digital supply chain finance model in Thailand was high suitability and can be appropriately applied in actual work settings.